The Management of Dealls’ Social Media on X (Twitter) in Building Job Seeker Engagement and Trust - Al-Fallah, Sadila Syaumi; Sari, Wina Puspita; Soegiarto, Asep; Putriana, Muria; Kholik, Abdul (Journal of Research in Social Science and Humanities, 2025)
Social media has become a strategic channel for digital recruitment platforms to build relationships with their audiences. One platform actively fostering closeness with job seekers on X is @deallsjobs, the official account of Dealls, a recruitment platform known for being responsive and closely connected to the job-seeking community on social media. This study aims to understand how Dealls manages its X account to build engagement and trust among job seekers. Using a descriptive qualitative approach, the study applies Regina Luttrell’s Circular of SoMe model as the analytical framework. Data collection was conducted through direct observation, in-depth interviews with the key informant managing the X account and a job seeker, as well as documentation of posts from the @deallsjobs account on X. The data were analyzed through data reduction, data presentation, and conclusion drawing. The results show that Dealls implements the four stages of the Circular of SoMe in an integrated manner. In the Share stage, Dealls distributes job vacancy content, career education, and motivational posts in a contextual and responsive way in relation to public discussions. In the Optimize stage, the X account administrator adjust the posting times, communication tone, and relevant issues according to user characteristics, including tapping into ongoing trends. In the Manage stage, the account maintains consistency through polite and relevant communication, including careful responses to sensitive issues via cross-team coordination. Lastly, in the Engage stage, Dealls builds personal connections with the audience through two-way interactions, empathetic replies, and a casual yet meaningful tone of communication. The study concludes that Dealls' social media management goes beyond mere information dissemination; it also focuses on fostering strong digital relationships with its audience. Consistent, responsive, and relevant management practices drive active engagement and help build trust, stemming from timely responses, empathetic communication, and a presence that aligns with job seekers' needs on the X platform. The engagement and trust developed through these practices also open up opportunities for the emergence of long-term digital loyalty.